The value added statement : - Morley, Michael F. (Gee and Co. for the Institute of Chartered Accountants of Scotland, 1978)
Chapter 1. Reporting value added, Chapter 2. The value Added Statement: underlying concepts and some misconceptions,..., Chap 12. Conclusions and recommendation.